Evaluación del comportamiento de un sistema de almacenamiento Ongrid. - Paredes Paredes, Jhony Manuel (2023)
The present research study focused on evaluating the economic viability of the use of energy storage systems applied to industry. Through an exhaustive bibliographical review, a methodology was determined that allowed the development of various study scenarios, all aimed at determining the economic viability of these systems. For this purpose, the excess energy from the storage system was analyzed using historical industry demand profile data (PROLATD) obtained from a study carried out in 2019, which served as a case study. The current regulations established by ARCERNNR, the regulator of the tariff schedule, were applied. In addition, Excel software was used for the analysis of electricity rates and economic evaluation. The results revealed that by reducing the maximum peak to 7% using 3 battery modules, an annual savings of $2417.40 was achieved. These results proved to be profitable, with a Net Present Value (NPV) of $5617.19 and an Internal Rate of Return (IRR) of 14%. However, by reducing the peak to 16% with 7 battery modules, an annual saving of $2711.97 was obtained, but with a NPV of $-4896.53 and an IRR of 5%. These financial indicators suggest that this scenario is not profitable due to the increased investment required. It is worth mentioning that the economic evaluation was carried out with a discount rate of 7.99% and a time horizon of 25 years. The need to replace the equipment at 15 years due to its useful life and deterioration was also considered. In this way, it was possible to verify the economic feasibility of the project, considering all relevant aspects. Finally, it was verified that the proposed system also contributes to the reduction of the demand charge during peak hours.